Elites and democratic development in Russia - Steen, Anton, 1949-; Gelʹman, Vladimir, 1965- (London ; New York : Routledge, 2003)
The transformation from Communist rule towards democratic development in Russia cannot be fully understood without taking the elites into full consideration. Elites and Democratic Development in Russia examines how elites support and challenge democracy and why they are crucial to Russian democracy in particular. In this innovative volume, twelve respected scholars investigate how elites have affected the transition from Communist rule towards democratic development in Russia. They discuss how the elites' degree of integration on national and regional levels may constitute the main.
Elites and democratic development in Russia : an introduction / Vladimir Gelʹman and Anton Steen -- Political elite integration and differentiation in Russia / John Higley, Oksan Bayulgen, Julie George -- Russia's elites in search of consensus : what kind of consolidation? / Vladimir Gelʹman -- The elite basis of Yeltsin's and Putin's regimes / Anton Steen -- The rise and fall of the Russian governor : institutional design vs patron/client relationships / Helge Blakkisrud -- Between centre and regions : the State Duma deputies and Russian federalism / Anton Steen and Vsevolod Timofeev -- Party extinction in Russia, 1993-2002 : an elite connection / Grigorii V. Golosov -- Local elites in Russia's transition : generation effects on adaptation and competition / James Hughes and Peter John -- Reforms and orientations of regional elites : the case of St. Petersburg / Alexandr Duka -- Elite transformation and regime change : the case of Tomsk Oblast / Inessa Tarusina -- Studies of political elites in Russia : an overview / Vladimir Gelʹman and Inessa Tarusina.
"Simultaneously published in the USA and Canada"--Title page verso
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Elite (Social sciences) -- Russia (Federation); Political leadership -- Russia (Federation); Russia (Federation) -- Politics and government -- 1991-; Democracy -- Russia (Federation); Post-communism.; Élite (Sciences sociales) -- Russie; Postcommunisme; SOCIAL SCIENCE -- Social Classes; Democracy; Elite (Social sciences); Political leadership; Politics and government; Post-communism; Russia (Federation); Since 1991